A Micro Exploration into Learner's Dictionaries: a Prototype Theoretical Perspective. (17th November 2015) - Jiang, Guiying; Chen, Qiaoyun
Abstract: This paper examines the application of prototype theory to definition in the five major English learner's dictionaries, with a focus on the analysis of the microstructures employed for sense differentiation and ordering. The issues covered in this study include: (1) the treatment and utilisation of prototypicality, non-prototypicality, family resemblance and the shift and split of prototype pertaining to semantic change in sense differentiation (including illustration); (2) the arrangement of prototypical and non-prototypical senses as well as the illumination of sense relations in sense ordering. It has been demonstrated that the theory has found unconscious and scattered application in these dictionaries, the underlying reasons for which are subsequently explored. Readers are cautioned to the deficiencies of prototype theory in definition and corresponding suggestions are offered for better application of the theory and for greater user-friendliness.